Perancangan Video Campaign Clenore Pictura Untuk Menampilkan Personal Branding Dan Brand Value - Christy Cahyadi; Rendy Iswanto (Jurnal Vicidi, 2022)
Clenore Pictura is a business that focuses on hand-drawn face services, which has been established for 4 years, from 2018. So far, Clenore has only shared the painting through social media and marketing by word of mouth. After evaluation, this strategy haven't shown the personal branding and brand value of Clenore Pictura. This study aims to find out what the right one brand campaign to show personal branding and brand values ​​that are appropriate for Gen Z, 18-23 years old girls. This study uses primary data collection methods, through interviews with expert users and extreme users as well as surveys and data collection, through literature studies from national and international books and journals in the last 10 years that discuss communication strategies for Clenore Pictura. The results of this study found that the right strategy to display personal branding and brand value is to use a video campaign. Keyword : personal branding, brand value, video campaign, brand communication, art and craft.